Pengaruh Model Pembelajaran Kooperatif Tipe STAD Berbantuan Alat Peraga Al-Qur’an untuk Meningkatkan Penguasaan Tajwid - Ma'ruf, Ma'ruf Ishak Ola (Indo-MathEdu Intellectuals Journal, 2024)
The lack of mastery of tajweed in reading the Qur'an in the subject of Al-Qur'an Hadith so that the researcher uses a STAD-type cooperative learning model assisted by Qur'an teaching aids to improve the mastery of tajweed. This study uses a quantitative research method with a type of field research. The data collection technique used by observation and tests. The data analysis technique uses test question analysis, analysis of increasing tajweed mastery, analysis of the effectiveness of using the learning model. The results of this study are the average score of the pre-test of the experimental class of 57.8571 and the average score of the post-test of the experimental class of 78.8095 with the N-gain of the experimental class of 0.5071. Meanwhile, for the kontrol class, the average score of the Pre-test was 26,667 and the average score of the post-test was 59,667. With an N gain of 0.34035. This shows that the STAD type cooperative learning model has a greater influence on increasing the mastery of tajweed of MTs Negeri 2 Alor students. Based on the analysis, Cohen's f value of 0.139 was obtained with medium effect interpretation, meaning that the cooperative learning model had a sufficient effect on the increase in tajweed mastery of grade VIII students